QuaPra: Efficient transcript assembly and quantification using quadratic programming with Apriori algorithm - Ji, Xiangjun; Tong, Weida; Ning, Baitang; Mason, Christopher E.; Kreil, David P.; Labaj, Pawel P.; Chen, Geng; Shi, Tieliu (Science China. Life sciences, 2019)
RNA sequencing (RNA-seq) has greatly facilitated the exploring of transcriptome landscape for diverse organisms. However, transcriptome reconstruction is still challenging due to various limitations of current tools and sequencing technologies. Here, we introduce an efficient tool, QuaPra (Quadratic Programming combined with Apriori), for accurate transcriptome assembly and quantification. QuaPra could detect at least 26.5% more low abundance (0.1–1 FPKM) transcripts with over 2.1% increase of sensitivity and precision on simulated data compared to other currently popular tools. Moreover, around one-quarter more known transcripts were correctly assembled by QuaPra than other assemblers on real sequencing data. QuaPra is freely available at https://doi.org/www.megabionet.org/QuaPra/ .